[dr. Katalin Pető 4]
resting & playing on the field, cog railway, girl & parents, Szeged Tisza-beach, girl playing, birthday-cake with 3 candle & children, in the playground, snowman & sledging, girl with scooter, Moszkva-square, Pioneer Railway, Zoo, children's performance, Palatinus open-air bath, girl doing gymnastics, girl with bicycle in Szeged Dóm-square, girl & grandmother around the house,1955 annual school-report, Balaton, girl & boy riding a bicycle hand in hand